Pinpointing Failure Inducing Event Orderings - Mercan, Hanefi; Yilmaz, Cemal (2014 IEEE International Symposium on Software Reliability Engineering Workshops, 2014)
A new method is designed to pinpoint failure inducing event orderings in Event Based Systems. Sequence Covering Arrays are used as test suites for systems under test which have only deterministic type of failures. After testing all test cases of SCA to get full coverage on event orderings of length 2 and 3, new test cases are generated using a new method inspired from Delta Debugging Algorithm. Suspicious set of event orderings which are most likely failures, are constructed for each failure type, and this sets are narrowed down adaptively with the result of newly generated test cases. Experiments are carried out with different fault scenarios. Our results suggest that proposed algorithm can detect all failure inducing event orderings using small number of extra test cases.